2021
DOI: 10.1155/2021/4376366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Conventional Water‐Based Mud Characteristics by Applying Zinc Oxide and Silica Dioxide Nanoparticle Materials for a Selected Well in the Kurdistan/Iraq Oil Field

Abstract: Nanomaterials have gained a wide interest in the oil and gas industry due to their immense applicability. Nanomaterials are being used to formulate a new generation of drilling mud known as Nanomud or Smart mud, where it has the ability to improve mud properties and eliminate borehole problems. Using nanoparticles as an additive agent in conventional drilling mud can lead to a more efficient drilling process in troublesome formations. In this study, several conventional water-based muds from a selected well dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Differential pressure adhesion, caused by cake buildup on the wellbore wall, increases the risk of drilling tool damage [28]. In order to prevent drilling fluid from escaping and entering a formation, NPs can be used to obstruct the pore space [7]. Fig.…”
Section: Loss Of Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential pressure adhesion, caused by cake buildup on the wellbore wall, increases the risk of drilling tool damage [28]. In order to prevent drilling fluid from escaping and entering a formation, NPs can be used to obstruct the pore space [7]. Fig.…”
Section: Loss Of Filteringmentioning
confidence: 99%
“…Pipe sticking and mud loss are two problems that can arise as a result of poor drilling fluid design. Poor mud design can lead to other problems, such as bit balling and borehole collapse [7].…”
Section: -Introductionmentioning
confidence: 99%
“…By their small size, nanoparticles bridge gaps in the formation's porous structure and effectively seal and plug them. They prevent fluid leakage, particularly in shale formations [10]. Some researchers, however, have shown that certain nanoparticles can improve the performance of polymer-based drilling fluids by improving their rheological, filtration, and lubrication characteristics [11].…”
Section: Introductionmentioning
confidence: 99%